Probiotics and dietary intervention modulate the colonic mucosa-associated microbiota in high-fat diet populations - Qian, Leimin; Huang, Jianming; Qin, Huanlong (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Alterations in the gut microbiota due to a high-fat diet and diet-induced illness have been found in both mouse models and humans. Observational studies suggest that probiotic administration and diet shifts may treat diet-related diseases. However, the effect of these interventions on the colonic mucosa has not yet been elucidated. This study investigated the efficacy of probiotic supplementation and dietary intervention as prophylactic tools under high-fat diet conditions. Materials and Methods: A total of 36 volunteers that normally consumed a high-fat diet were enrolled and treated with either a control diet, a low-fat dietary intervention, Bifidobacterium triple viable capsule therapy, or a combination of a low-fat diet and Bifidobacterium triple viable capsule therapy. Pyrosequencing of the V3 and V4 regions of the 16S rRNA genes was conducted to determine the extent to which probiotics and dietary intervention altered the mucosal microbiota. Results: This study demonstrated that interventional treatment with probiotics and a low-fat diet increased the diversity of the mucosal microbes, dietary intervention alone produced the most significant effect, whereas the combined intervention exhibited no synergetic improvement. Pyrosequencing demonstrated that probiotics and dietary intervention significantly elevated the abundance of some bacterial taxa assigned to the phylum Firmicutes and the beneficial genera Prevotella, Gemmiger, Coprococcus, and Faecalibacterium and reduced some harmful bacterial taxa assigned to the phylum Proteobacteria and genus Streptophyta. Conclusion: The results of this study suggested that the addition of probiotics and dietary intervention could improve the composition of the colonic mucosal microbiota in high-fat diet populations.